The 1755 Lisbon Tsunami at Vila do Bispo municipality, Portugal - Santos, Angela (2015)
The numerical model of the 1755 Lisbon Tsunami was conducted at Vila do Bispo municipality. The tsunami source area of this historical event is assumed to be on the Gorringe Bank. Numerical model results of historical data have been validated by a combined analysis of eyewitnesses’ accounts, field surveys, geological records and archeological findings (conducted by previous authors). The coastal area has remained a mostly natural landscape since the 18th century, with popular beaches that increase the population potentially exposed to a tsunami, especially one occurring in summer. For these reasons, we use local tsunami hazard assessment as a criterion varying between moderate and critical. Results also show that the 16 low ground areas we surveyed were inundated between 15 and 30 minutes after the earthquake. For this reason, persons should act quickly in future to evacuate areas immediately after an earthquake and to move to higher ground. Results also show that safe, swift evacuation may be difficult in 50% of these areas, endangering special populations such as tourists. Tsunami information boards should therefore be put on beaches and evacuation exercises and drills should be implemented and practiced regularly.